The effect of Milling Time on Crystal size Sandvik Sanergy - Qolby Sabrina; Ahmad Afandi; Nurhalis Majid (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
Preliminary study material sandvik sanergy as an alternative material for interconnect applications solid oxide fuel cell (SOFC) have been conducted. Sandvik sanergy was milled for 0, 8, 24, and 48 hr with ball milling planetary MTI Corp. The physical properties of small grain size can affect the strength of the alloy when applied as interconnect. In this study, ratio between ball miller and sandvik sanergy was 1:10 aiming to obtain a small grain size. Crystal size characterized by XRD Rigaku Smartlab, morphology of sandvik sanergy after milling observed using SEM Hithaci SU3500 20 kV. Diameter of particles were observed by particle size analyzer (PSA). Results showed that crystal size as well as particle size tended to decrease with the increasing milling time. Discrepancy occurred at 24 hour of milling time and showed agglomeration.©2020 JNSMR UIN Walisongo. All rights reserved.